Big data security features and operation practices - Zhiyong LIU; Zhongjiang HE; Yilong RUAN; Junfeng SHAN; Chao ZHANG (Dianxin kexue)
With the continuous refinement of data types, user roles and application requirements, as well as the complex data storage and flow scenarios of big data, the requirement of big data security is higher and higher.Starting from the security characteristics and operation practice of big data, the security characteristics and technology development trend of big data were analyzed, the construction and operation practice of China Telecom’s big data security defense system with “data and people” as the core was systematically summarized.Some thoughts and prospects for the introduction of new technologies were also raised such as blockchain, federated learning, artificial intelligence and zero trust in data security circulation, data security risk monitoring and data access control.